Copper-catalyzed sulfonylation of N-tosylhydrazones followed by a one-pot C–N bond formation. Issue 24 (28th May 2021) - Zhang, Kena; Provot, Olivier; Tran, Christine; Alami, Mouad; Hamze, Abdallah
Abstract : A new methodology to synthesize sulfonyl- N -phenylaniline derivatives via the trapping of bromo-sulfone derivatives generated from N -tosylhydrazones (NTHs) with amines is described. Abstract : A new methodology to synthesize sulfonyl- N -phenylaniline derivatives via the trapping of bromo-sulfone derivatives generated from N -tosylhydrazones (NTHs) with amines is described. The reaction proved successful for a wide range of NTHs and amines and tolerated various functional groups on either coupling partner (35 examples). The mechanism was studied, and we showed that the sulfone formation does not follow a radical pathway.